Marked gender differences in progression of mild cognitive impairment over 8 years - Lin, Katherine A. (Alzheimers Dement (N Y), 2015)
INTRODUCTION: This study examined whether, among subjects with mild cognitive impairment (MCI), women progressed at faster rates than men. METHODS: We examine longitudinal rates of change from baseline in 398 MCI subjects (141 females and 257 males) in the Alzheimer's Disease Neuroimaging Initiative-1, followed for up to 8 years (mean, 4.1 ± 2.5 years) using mixed-effects models incorporating all follow-ups (mean, 8 ± 4 visits). RESULTS: Women progressed at faster rates than men on the Alzheimer's disease assessment scale-cognitive subscale (ADAS-Cog; P = .001) and clinical dementia rating-sum of boxes (CDR-SB; P = .003). Quadratic fit for change over time was significant for both ADAS-Cog (P = .001) and CDR-SB (P = .004), and the additional acceleration in women was 100% for ADAS-Cog and 143% for CDR-SB. The variability of change was greater in women. The gender effect was greater in apolipoprotein E (APOE) ε4 carriers. DISCUSSION: Women with MCI have greater longitudinal rates of cognitive and functional progression than men. Studies to confirm and uncover potential mechanisms appear to be warranted. TRIAL REGISTRATION: ADNI ClinicalTrials.gov identifier: NCT00106899.